AIE-active light up probe for sensitive detection of amine vapors and its practical application in food spoilage monitoring. (21st March 2023) - Ding, Ge; Wang, Xinchao; Ling-hu, Changxin; Fan, Yinjie; Zhou, Linling; Luo, Derong; Meng, Suqi; Meng, Jiangping; Chen, Wei; Liu, Yao; Gao, Guangyong; Peng, Di
Abstract: Amines act as a crucial role in agricultural field, chemical and food industries, but volatile amine vapor will cause environmental pollution and threat to human health. Thus, design and development of probes for amine vapor detection possesses great application potential. However, some already existing fluorescent probes for amine vapor detection generally exist some defects, such as easily suffering from aggregation caused emission quenching (ACQ) effect. In this work, a simple fluorescent sensor DEMCA-PA for light-up detection of amine vapor was successfully constructed, and DEMCA-OH produced via DEMCA-PA interacting with ammonia displayed remarkable aggregation-induced emission (AIE) properties. Thus, a portable probe for amine vapor recognition was constructed via depositing DEMCA-PA on filter paper, this probe has good selectivity, fast response time, high sensitivity, and lower detection limit (7.9 ppm), the mechanism was further confirmed by DFT calculations and UV-spectra property and HPLC analysis. Given its unique recognition effect for NH3, the probe DEMCA-PA could also be applied in food spoilage detection field. Graphical abstract: Image 1 Highlights: Designed and constructed a portable ESIPT combines AIE "light-up" fluorescent sensor DEMCA-PA for ammonia vapor detection. Detection for ammonia vapor with good selectivity, fast response time, high sensitivity, and real-time response. The portable DEMCA-PA sensor realized its practical application in food spoilage monitoring and fluorescent invisible materials fields.